1D micro-nanopatterned integrin ligand surfaces for directed cell movement - Levario-Diaz, Victoria; Alvarado, Rebecca Elizabeth; Rodriguez-Quinteros, Cristina Marcela; Fink, Andreas; Christian, Joel; Feng, Wenqian; Cavalcanti-Adam, Elisabetta Ada (Frontiers in Cell and Developmental Biology, 2022)
Cell-extracellular matrix (ECM) adhesion mediated by integrins is a highly regulated process involved in many vital cellular functions such as motility, proliferation and survival. However, the influence of lateral integrin clustering in the coordination of cell front and rear dynamics during cell migration remains unresolved. For this purpose, we describe a novel protocol to fabricate 1D micro-nanopatterned stripes by integrating the block copolymer micelle nanolithography (BCMNL) technique and maskless near UV lithography-based photopatterning. The photopatterned 10 μm-wide stripes consist of a quasi-perfect hexagonal arrangement of gold nanoparticles, decorated with the RGD (arginine-glycine-aspartate) motif for single integrin heterodimer binding, and placed at a distance of 50, 80 and 100 nm to regulate integrin clustering and focal adhesion dynamics. By employing time-lapse microscopy and immunostaining, we show that the displacement and speed of fibroblasts changes according to the nanoscale spacing of adhesion sites. We found that as the lateral spacing of adhesive peptides increased, fibroblast morphology was more elongated. This was accompanied by a decreased formation of mature focal adhesions and stress fibers, which increased cell displacement and speed. These results provide new insights into the migratory behavior of fibroblasts in 1D environments and our protocol offers a new platform to design and manufacture confined environments in 1D for integrin-mediated cell adhesion.